1970
DOI: 10.3329/jbcps.v26i1.4228
|View full text |Cite
|
Sign up to set email alerts
|

Dynamics of Spirulina in Promoting Health Benefits for Arsenicosis Patients

Abstract: A total number of 40 patients affected with arsenicosis were selected and clinically examined prior to feeding trials. The interrelatedness between improvement respondents following spirulina intake in respect of age, sex, nutrition and social condition of patients exposed to arsenic contaminated water was evidenced. Among sexwise respondents about 62% females showed improvement in comparison to 58.3% males. The spirulina intake caused more improvements in age group 15-35 years (66.66%) than patients of 35 to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Spirulina effectively promotes cell rejuvenation and, thereby, repairs liver and kidney tissue damage (Khan et al 2001). In addition, spirulina has a protective effect against arsenic toxicity in humans (Misbahuddin et al 2006;Rahman et al 2008). Therefore, the aim of our investigation was to elucidate the role of the non-invasive oral application of spirulina in the amelioration of high dose arsenic-mediated uterine degeneration.…”
Section: Introductionmentioning
confidence: 99%
“…Spirulina effectively promotes cell rejuvenation and, thereby, repairs liver and kidney tissue damage (Khan et al 2001). In addition, spirulina has a protective effect against arsenic toxicity in humans (Misbahuddin et al 2006;Rahman et al 2008). Therefore, the aim of our investigation was to elucidate the role of the non-invasive oral application of spirulina in the amelioration of high dose arsenic-mediated uterine degeneration.…”
Section: Introductionmentioning
confidence: 99%
“…Spirulina (Spirulina platensis), a blue-green alga, is rich in protein, phytonutrients, antioxidants, and polysaccharides that might have mitigating effects against heavy metal poisoning. Spirulina has been recommended as a chemoprotective against arsenic-induced toxicity in humans (4,5). It seems reasonable to expect that administration of spirulina might provide a protective mechanism against arsenic-induced toxicity in goats.…”
Section: Introductionmentioning
confidence: 99%
“…It has been reported that Pc has significant antioxidant and radical scavenging properties, offering protection against oxidative stress 5 . In addition, spirulina plays a protective role against arsenic toxicity in human 6 .…”
Section: Introductionmentioning
confidence: 99%